(untitled) (Research, Society and Development, 2022)
The intensification of health sanitary standards for poultry farms had biosecurity consolidated from the appropriate normative instructions added. This adaptation led to the international recognition of the poultry industry in Brazil, one of the largest exporters of chicken meat in the world. The implementation of sanitary management should extend to free-range chickens, considering the culture rooted in free-range protein, which occupies a large national market. These measures reduce the risk of infections, enabling the health of the animal and protecting the health of the consumer. This study aimed to verify the incidence of hemoparasites in chickens (Gallus gallus domesticus) of artisanal breeding sold in street markets in the city of Porto Velho/RO. The experimental research took place in the period of 2022, from 11 blood samples collected by venipuncture, after the stunning process. In addition to parasite identification by morphology in OM through blood smear, blood count was also performed by hemocytometer (Neubauer chamber). Three species of hemoparasites were identified: Leucocytozoon (82%), Hemogregarin (18%) and Plasmodium (18%). Differential analysis of leukocytes showed parasitic infection with high rates of monocytes (14%) and heterophils (51%), confirming high parasitemia observed by microscopy. The results indicate multiple infections by vectors, suggesting that small breeding sites need management training, as well as the slaughtered species can be a potential reservoir compromising the health of other animals, such as man.